2023
DOI: 10.1108/josm-12-2021-0464
|View full text |Cite
|
Sign up to set email alerts
|

Self-service technology recovery: the importance of psychological need support

Abstract: PurposeThe service recovery literature provides little guidance to firms on how users of self-service technology (SST) perceive assistance provided by human and non-human service agents following a service obstacle. This research responds by addressing two important research questions about SST recovery: (1) how are perceptions of assistance provided following a service obstacle influenced by a customer's psychological needs? and (2) does supporting the psychological needs of customers positively impact contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…This supports previous findings, which found that when customers recognize the value of a behavior, they would feel more positive about it and be more inclined to perform that behavior (Osei-Frimpong, 2017; Wang and Hou, 2015). For example, engaging in self-recovery after an SST failure is a learning opportunity that helps customers better understand troubleshooting processes and gain experience in solving similar future problems (Keating and Aslan, 2023). Self-recovery will result in customers' increased ability, knowledge, skills and self-improvement (Dong et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This supports previous findings, which found that when customers recognize the value of a behavior, they would feel more positive about it and be more inclined to perform that behavior (Osei-Frimpong, 2017; Wang and Hou, 2015). For example, engaging in self-recovery after an SST failure is a learning opportunity that helps customers better understand troubleshooting processes and gain experience in solving similar future problems (Keating and Aslan, 2023). Self-recovery will result in customers' increased ability, knowledge, skills and self-improvement (Dong et al.…”
Section: Discussionmentioning
confidence: 99%
“…First, with research on SST failure and service recovery still in its early stage, most of the extant studies are based on situations where the service provider is involved in the service recovery process, either in the form of firm-recovery or joint-recovery (e.g. Dao and Theotokis, 2021; Keating and Aslan, 2023; Lee and Cranage, 2018; Mattila and Cho, 2011). This study extends prior studies by shifting the focus of academic inquiry to customers' self-recovery in a disrupted SST setting and shedding light on how intrinsic and extrinsic motivations stimulate customers to perform self-recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations